Mengemis Online di TikTok: Etika dan Perspektif Maslahah Mursalah - Tamsri, Muhammad Abdullah (Fawaid : Sharia Economic Law Review, 2024)
The rapid development of digitalization, unaccompanied by adequate preparedness, has given rise to the phenomenon of online begging on social media applications, including TikTok. This study aims to identify the true intentions behind online begging to provide the public with a clear distinction between being a content creator and an online beggar. Additionally, the research seeks to determine whether online begging is permissible in Islam from the perspective of Maslahah Mursalah. This research adopts a normative empirical legal approach using the analytical approach. Data collection techniques include observation, interviews, and documentation. The findings of this research reveal the following (1)The practice of online begging on TikTok's live streaming feature is carried out by showcasing their disadvantaged conditions, appealing to viewers' sympathy, and requesting gifts during the live stream.(2)From the perspective of Maslahah Mursalah, begging based on urgent needs and daily necessities is permissible as long as there is no exploitation involved and the funds received are properly allocated for essential needs. Meanwhile, online begging driven by emotional empathy or entertainment is also allowed but should not become a means of livelihood dependence. Islamic law encourages effort and work. Furthermore, entertainment activities presented during live streaming should provide benefits and avoid self-harm. Kata Kunci: Pengemis Online, TikTok, Maslahah Mursalah